Efficacy of Transconjunctival Tucking Surgery in Comparison With the Phenylephrine-test Positive and Negative Involutional Blepharoptosis Groups - Kosuke Ogasawara, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. This study aimed to determine whether there is a significant difference in the efficacy of transconjunctival tucking of the Müller muscle and levator aponeurosis in patients with involutional blepharoptosis who tested positive or negative on the phenylephrine test. Methods:. The analysis involved 64 eyes of 42 patients with levator muscle function of the upper eyelid of 8 mm or more and a margin reflex distance 1 (MRD-1) of less than 2 mm. Patients who tested positive and negative for 5% phenylephrine were allocated to group A (41 eyes of 26 patients) and group B (23 eyes of 16 patients), respectively. The efficacy of surgery (ΔMRD-1) was compared by subtracting preoperative MRD-1 from postoperative MRD-1. Multiple comparison tests were performed to evaluate changes in MRD-1 and ΔMRD-1 every 3 months from 3 to 12 months after transconjunctival tucking of the Müller muscle and levator aponeurosis. Results:. Regarding the mean ΔMRD-1 values at 3, 6, and 12 months postoperatively, the values at 6 and 12 months were significantly lower in group A than in group B, with 2.31, 1.98, and 1.81 mm, respectively, in group A and 2.73, 2.71, and 2.50 mm, in group B (P = 0.03 at 6 mo and P = 0.041 at 12 mo). Conclusions:. The efficacy of transconjunctival tucking of the Müller muscle and levator aponeurosis was greater in group B than in group A, and the results were more stable. This is an interesting finding when considering the successful mechanism in the present surgical method.